PENYEBAB RUJUKAN PENYAKIT NON SPESIALISTIK KE FASILITAS KESEHATAN TINGKAT LANJUT PADA PUSKESMAS DI POLEWALI MANDAR - Sarina, Nitha; Amelia, Andi Rizki; Hamzah, Wardiah (Universitas Islam Negeri Alauddin Makassar, 2024)
Background: There were cases of referral for non-specialist diseases to advanced health facilities at the Community Health Center in Polewali Mandar Regency. Objective: This study aims to obtain information on the causes of referral for non-specialist diseases to advanced health facilities at the Community Health Center in Polewali Mandar Regency. Methods: This research uses a qualitative approach with a case study design. The key informant in this research is the head of the Community Health Center in Polewali Mandar, and the main informant in this research is the doctor who works at ten Community Health Centers in Polewali Mandar. Data validity using source triangulation method. Results: The research results show that the doctor's understanding of the function of the community health center as a gatekeeper has been optimal according to competency standards, standard operational procedur for patient referral are available in all health centers, the facilities and infrastructure at the health center in Polewali Mandar are not yet fully available, the factor of drug availability at the Community Health Center is the cause of referral of non-specialist diseases to advanced health facilities because the medicines are incomplete, and therenis requests for patients to be referred without indication of referral to advanced health facilities but doctors do not provide referrals and provide education to patients. Conclusion: The results of the research show that the doctor's understanding of the Community Health Center as a factor gatekeeper, standard operational procedures that serve as referral guidelines, the availability of health workers at the Community Health Center, patient requests to be referred without indication of referral, are not the causes of referrals for non-specialist diseases to advanced health facilities from the Community Health Center in Polewali Mandar. Meanwhile, the availability of facilities and infrastructure at the Community Health Center and the availability of medicines at the Community Health Center are factors that influence referrals for non-specialist diseases to advanced health facilities from the Community Health Center in Polewali Mandar Regency.